Smart waste management system using IoT - Hasan, B.M Rakib; Yeazdani, A.M.M. Golam; Istiaque, Labib Md; Chowdhury, Rafee Mizan Khan (BRAC University, 2017)
Cataloged from PDF version of thesis report.